Procedures for Disability Issues in the Education of Education in Higher Education - Dheka Dwi Agustiningsih (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2017)
This paper discusses the issue of disability in universities that aims to discuss universities that must play a role and participate in the government and society to build and improve the lives of people with disabilities through the activities of Tridharma. The method used in this analysis is descriptive. The legal basis for persons with disabilities to obtain the right to education is the 1945 Constitution Article 31 paragraph 1 with the implementation of the paradigm of inclusive education in higher education reviewed by the Minister of Education and Culture No. 26 of 2014.  In Islam, disability is implied in the letter of At-tin verse 4 and Al-Hujurat verse 13. Understanding disability-friendly education is one of the obligations that must be implemented about human beings and with the constitution through: (1) The equivalent to register; (2) freedom of choice of study program/department; (3) providing services as needed.Keywords: Disabilities’, Streaming, dan Higher Educational. Abstrak Tulisan ini membahas isu disabilitas di perguruan tinggi yang bertujuan untuk membahas tentang perguruan tinggi yang harus berperan dan berpartisipasi bersama pemerintah dan masyarakat untuk membangun dan meningkatkan taraf hidup penyandang disabilitas melalui kegiatan Tridharma. Metode yang digunakan dalam analisis ini adalah deskriptif. Adapun landasan hukum bagi penyandang disabilitas mendapatkan hak pendidikan adalah UUD 1945 Pasal 31 ayat 1 dengan implementasi paradigma pendidikan inklusif di pendidikan tinggi yang diulas sesuai dengan peraturan Menteri Pendidikan dan Kebudayaan Nomor 26 Tahun 2014. Dalam Islam disabilitas di antaranya disiratkan dalam surat At-tin ayat 4  surat Al-Hujurat dan  ayat 13. Memahami pendidikan yang ramah terhadap penyandang disabilitas merupakan salah satu kewajiban yang harus dilaksanakan dalam rangka hubungan dengan manusia dan dengan konstitusi melalui: (1) pemberian kesempatan yang setara untuk mendaftar; (2) kebebasan memilih program studi/jurusan; (3) pemberian layanan sesuai dengan kebutuhan.Kata kunci: Disabilitas, Pengarusutamaan, dan Perguruan Tinggi.